2016
DOI: 10.1590/0001-3765201620150553
|View full text |Cite
|
Sign up to set email alerts
|

Are salty liquid food flavorings in vitro antitumor substances?

Abstract: The objective of this study was to evaluate the antiproliferative, cytotoxic and genotoxic potential of salty liquid synthetic flavorings of Butter, Cheddar Cheese and Onion. The antiproliferative potential (2.9-1500 µg/mL) was assessed by MTT assay after 72h using the human tumor lines SF-295 (glioblastoma), OVCAR-8 (ovarian), HCT-116 (colon) and HL-60 (promyelocytic leukemia) and primary cultures of murine Sarcoma 180 (S180) and peripheral blood mononuclear cells (PBMC). Allium cepa bulbs were exposed to gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Such cytotoxic compounds, for the most part, have the potential to significantly impair the growth and function of the organs in which they are acting. Complementing the information of Caritá and Marin-Morales (2008), Gomes et al (2013); Sales et al (2017); Moura et al (2016) and Carvalho et al (2016) state that the inhibition of cell proliferation by cytotoxic compounds in tissues of high cell proliferation and normal functioning and/or without cell changes -again mentioning here the root meristems used as bioassays in the present study -is quite detrimental to the organism by inhibiting or limiting the replenishment of cells, altering the production of proteins and, consequently, resulting in malfunctioning of the organ or tissue where it is located. Table 2 shows that all analyzed milk samples, at a concentration of 0.065 g /mL and at 24 hour exposure time, promoted a significant number of cellular alterations in the meristematic tissue of the roots, proving to be genotoxic.…”
Section: Resultsmentioning
confidence: 99%
“…Such cytotoxic compounds, for the most part, have the potential to significantly impair the growth and function of the organs in which they are acting. Complementing the information of Caritá and Marin-Morales (2008), Gomes et al (2013); Sales et al (2017); Moura et al (2016) and Carvalho et al (2016) state that the inhibition of cell proliferation by cytotoxic compounds in tissues of high cell proliferation and normal functioning and/or without cell changes -again mentioning here the root meristems used as bioassays in the present study -is quite detrimental to the organism by inhibiting or limiting the replenishment of cells, altering the production of proteins and, consequently, resulting in malfunctioning of the organ or tissue where it is located. Table 2 shows that all analyzed milk samples, at a concentration of 0.065 g /mL and at 24 hour exposure time, promoted a significant number of cellular alterations in the meristematic tissue of the roots, proving to be genotoxic.…”
Section: Resultsmentioning
confidence: 99%
“…The cytotoxicity of powdered milk samples against Vero cells was evaluated by the MTT (4,5dimethylthiazol-2-yl)-2,5diphenyl tetrazolium bromide (Sigma-Aldrich, Germany) method, by counting the number of viable cells (Marques et al, 2015;Carvalho et al, 2016). The cells were cultured in 96-well plates (TPP, Trasadingen, Switzerland), at a density of 2 × 10 5 cells well -1 .…”
Section: Cytotoxic Activity Evaluation By Mtt Methodsmentioning
confidence: 99%
“…Plant bioassays are considered satisfactory for monitoring the cytotoxic effects of chemical compounds (Carvalho et al, 2016) and meristematic root cells of Allium cepa (onion) have been indicated as an efficient test organism in the evaluation of cellular toxicity (Caritá & Marin-Morales, 2008), such as for example artificial food additives (Türkoğlu, 2007;Lacerda, Malaquias, & Peron, 2014) and processed foods (Türkoğlu, 2007;Carvalho et al, 2017). The A. cepa bioassay has excellent kinetic properties of proliferation and large and few chromosomes (2n = 16), which facilitates analysis for detection of changes in the cell cycle (Herrero et al, 2012;Neves, Ferreira, Lima, & Peron, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The root meristem of Allium cepa L. (onion) is considered in the scientific milieu as an efficient bioassay for the evaluation of the acute toxicity at the cellular level of chemical compounds due to the reduced chromosome number (2n = 16), which favors detection of chromosomal or clastogenic alterations, mitotic spindle disturbances or aneugenic alterations, and disorders in the cell proliferation index. This test system is internationally accepted by research agencies as an assessment tool with accurate sensitivity for analysis of cytotoxicity, genotoxicity and mutagenicity of the substance of interest, since the results achieved demonstrate, in most cases, satisfactory similarity to those obtained though animal testing systems and in cell cultures Herrero et al [10], Neves et al [11], Lacerda et al [12], Tabrez et al [13]; Gomes et al [14], Oliveira et al [15]; CAMPOS & MarinMorales [16]; Moura et al [17], Santana et al [18].Therefore, the goal of this study was to evaluate the cytotoxicity and genotoxicity of diet shakes in root meristem cells of A. cepa, from three different highly commercialized brands in drugstores all over Brazil.…”
Section: Introductionmentioning
confidence: 99%